2006
DOI: 10.1116/1.2187998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the NiFe sputter etch process in a rf plasma

Abstract: The sputter etching of NiFe thin films by Ar ions in a rf plasma has been studied and characterized with the use of a Langmuir probe. The NiFe sputter etch rate was found to depend strongly on incident ion energy, with the highest NiFe etch rates occurring at high rf bias power, low pressure, and moderate rf source power. NiFe etch rates initially increased with increasing rf source power, then saturated at higher rf source powers. Pressure had the weakest effect on NiFe etch rates. Empirically determined sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We can apply an Ar sputter etch process with the usual plasma etch apparatus. 25) One of the authors reported that the process showed almost the same performance with Ar milling. The major difficulty in the Ar sputter etch process was an electrical short failure due to conductive redeposition at the side wall of the MgO barrier.…”
Section: Introductionmentioning
confidence: 96%
“…We can apply an Ar sputter etch process with the usual plasma etch apparatus. 25) One of the authors reported that the process showed almost the same performance with Ar milling. The major difficulty in the Ar sputter etch process was an electrical short failure due to conductive redeposition at the side wall of the MgO barrier.…”
Section: Introductionmentioning
confidence: 96%
“…15 24 Previously, ion beam etching (IBE) has been used for the etching of MTJ materials by using Ar ions; however, due to the lack of volatile compounds during the etching, heavily redeposited etch residue was observed on the surface and sidewall of the etched MTJ features when the MTJ pattern was not severely over-etched. [25][26][27] In this current study however, instead of an Ar ion beam, a reactive ion beam (RIB) etching system was investigated in the etching of MTJ materials to increase the volatility of etch residue formed during the etching with reactive gases. For the effective etching of MTJ patterns, various etch gases such as Ar, NF 3 , CH 3 OH, and CO/NH 3 gas mixture were used and their etch characteristics were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, up to now, the metals used in magnetic devices have been etched by Ar ion milling [4][5][6] or pure Ar ion etching. 7) Wafer tilt and rotation allow for the removal of redeposited metals on the pattern side wall in the Ar ion milling process. However, it is difficult to utilize the technique for manufacturing VLSIs with high density, as it causes a shadow effect depending on the angle of the incident ion beam and pattern height.…”
Section: Introductionmentioning
confidence: 99%